If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 11y = 6x + 3y Solving 5x + 11y = 6x + 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 5x + -6x + 11y = 6x + -6x + 3y Combine like terms: 5x + -6x = -1x -1x + 11y = 6x + -6x + 3y Combine like terms: 6x + -6x = 0 -1x + 11y = 0 + 3y -1x + 11y = 3y Add '-11y' to each side of the equation. -1x + 11y + -11y = 3y + -11y Combine like terms: 11y + -11y = 0 -1x + 0 = 3y + -11y -1x = 3y + -11y Combine like terms: 3y + -11y = -8y -1x = -8y Divide each side by '-1'. x = 8y Simplifying x = 8y
| 2x+5=8x-4 | | Abx^2-(a+b)x+1=0 | | 10(x-2)=12 | | 10(e-2)=12 | | 10(0-2)=12 | | 10+N+N=18 | | b=351655c-1x-1 | | 351655=bxc | | (5X+6)-(-3x+10)=2x-4 | | 3(x+3)-7=4(x-2)+5 | | 6(x+13)=7x-8-3x | | 0.009x+0.2(500-x)=0.03*500 | | 3Y-2Z=-5 | | 4[x-1]=0 | | sin(3pix)=1 | | 3x(1+x)=0 | | 5x*2-7x-24=0 | | (x-3)(x-5)=64 | | (x-3)(x-5)=74 | | (x-3)(x-5)=84 | | (x+3)(x-5)=84 | | 3*x-x*log(x)=log(e^5) | | 3x-xln(x)=lne^5 | | 5x-7x-24=0 | | 4d^2-16-8d-d^2=0 | | x^3-24x^2+180x-424=0 | | 3x-xln(x)-9=(-4) | | 48=5x-28 | | 5+7x=9x-12 | | Log(x)12=5 | | y*(-3-y)=-10 | | -3y-y=-10 |